The impact of perceived social support on quality of life in patient awaiting for coronary artery bypass grafting (CABG) Surgery - Thandar Soe, Sumaiyah; Chong, Mei Chan; Kuar Surat Singh, Surindar (2015)

(untitled)
Purpose of the study Perceived social support has been of concern among patients who are awaiting Coronary Artery Bypass Grafting (CABG) surgery, yet the level of social support and its effect on an individual's quality of life are inconclusive. This study aimed to survey perceived social support and its effect on quality of life in patients awaiting CABG surgery at Outpatient Department of National Heart Institute, Malaysia. Methods In this cross-sectional study, we surveyed perceived social support and its effect on quality of life in 317 patients awaiting CABG surgery at Outpatient Department of National Heart Institute. All participants completed the 12-item Multidimensional Scale of Perceived Social Support (MSPSS) and 26-item World Health Organization Quality of Life (WHO- QOL) questionnaires. Results Out of 317 respondents, 242 (76.3%) patients reported poor quality of life. However those aged between 31-50 years and Chinese patients reported significantly higher quality of life as compared to other groups with p-value of <0.05 in ANOVA test. Perceived social support was positively correlated with their quality of life in Pearson correlation test. A linear regression analysis confirmed that there was an association between perceived social support and quality of life with r-value of 0.59. Conclusion Evidence indicates that patients who perceived receiving social support while awaiting for their CABG surgery had better quality of life. The results from this study can facilitate health care personnel to design an appropriate structured pre-operative assessment on social support and education program for patients awaiting CABG surgery to improve their quality of life.